Concur 2005 - concurrency theory proceedings - Abadi Martin ed.; International Conference on Concurrency Theory, CONCUR 2005; International conference on concurrency theory, CONCUR 2005 San Francisco, CA 23-26 Aug 2005 (Berlin Springer-Verlag, 2005)
Among the topics covered are concurrency related aspects of models of computation, Petri nets, model checking, game semantics, process algebras, real-time systems, verification techniques, secrecy and authenticity, refinement, distributed programming, constraint logic programming, typing systems and algorithms, case studies, tools, and environment for programming and verification.
Keywords: Concurrency theory